“Like Nothing I’ve Seen Before”: A Qualitative Inquiry Into the Lived Experience of Competing in a Trail Running Event - Chambers, Timothy P.; Poidomani, Jennifer (Frontiers in Psychology, 2022)
Background: A recent upsurge in nature-based exercise research demonstrates the potential added benefits of exercising in this context compared to more urban ones. Yet there is a lack of qualitative research investigating the lived experiences of those who participate in nature-based exercise events. Objective: To explore the lived experience of individuals who were first-time participants in a nature-based running event. Method: Six participants who completed the Run Forrest trail run for the first time were individually interviewed. Semi-structured interviews were devised, and participants were invited to talk about their experiences of running in the event. Interviews were analysed using interpretative phenomenological analysis. Results: Following data analysis, two superordinate themes were constructed to resemble participant experiences. ‘Maintaining good health is vital’ reflected participants’ personal theory of health and their perceived benefits of exercise. ‘Nature as a special place’ reflected the atmospheric characteristics of the event, including the pre-event set-up and the actual running event itself. Conclusion: Analysis suggests that participants considered the event and natural environment to provide unique value adding opportunities that encouraged positive experiences. These results also reaffirm the positive benefits associated with nature-based exercise, including potential benefits to individual wellbeing. Further research in this context may strengthen our collective understanding regarding individual motivation towards such events.